(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article deals with the borrowings, which name the phenomena of a masscult; common paradigmatic and syntagmatic laws for common languages are found out; the expansion of dictionary structure common literature language is certified.